2023
DOI: 10.1007/s12028-023-01757-7
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medical Management of Aneurysmal Subarachnoid Hemorrhage

Abstract: Aneurysmal subarachnoid hemorrhage is a medical emergency that necessitates direct transfer to a tertiary referral center specialized in the diagnosis and treatment of this condition. The initial hours after aneurysmal rupture are critical for patients with aneurysmal subarachnoid hemorrhage, both in terms of rebleeding and combating the effect of early brain injury. No good treatment options are available to reduce the risk of rebleeding before aneurysm occlusion. Lowering the blood pressure may reduce the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…1 Although there have been provided some medical treatments to prevent rebleeding, it is theoretically di cult to prevent rebleeding because no effective drugs were found so far. 2 Therefore, available protective posttreatments against the rebleeding-induced brain injuries is important to improve the prognosis for SAH patients.…”
Section: Full Textmentioning
confidence: 99%
“…1 Although there have been provided some medical treatments to prevent rebleeding, it is theoretically di cult to prevent rebleeding because no effective drugs were found so far. 2 Therefore, available protective posttreatments against the rebleeding-induced brain injuries is important to improve the prognosis for SAH patients.…”
Section: Full Textmentioning
confidence: 99%
“…A ruptured aneurysm extravasates blood into spaces around the brain known as cisterns. Overall, the case fatality rate is ~30%, and others experience various physical and cognitive disabilities [1]. Previous studies have identified prognostic factors for aSAH, including increased age, a history of hypertension, and, notably, the extent of intracranial (subarachnoid) hemorrhage [2].…”
Section: Introductionmentioning
confidence: 99%
“…EBI has been acknowledged as a pivotal factor influencing poor functional and cognitive outcomes, although it has received limited attention until recently. The predominant focus in most studies has been preventing and treating arterial narrowing, commonly called vasospasm, and addressing DCI [1]. The timely and accurate prediction of patients' outcomes following aSAH is crucial for informed clinical decision-making and providing comprehensive information to patients and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Aneurysmal subarachnoid hemorrhage (SAH) is one of the most striking and devastating neurological disorders [ 1 ]. SAH affects most central nervous system dysfunctions, leading to deleterious systemic consequences such as takotsubo cardiomyopathy and neurogenic pulmonary edema [ 2 ]. Previous studies have suggested that severe hypoxemia due to acute post-SAH pulmonary edema can lead to a global decrease in cerebral perfusion and ischemia, thereby complicating intensive fluid management [ 3 ].…”
Section: Introductionmentioning
confidence: 99%